The role and place of federal state unitary enterprises in the sphere of state property management. - E. V. Gavrilin (Управленческие науки)
The article is devoted to the problem of the organization of professional management of objects of the treasury of the Russian Federation in the light of the goals and objectives defined by the State Program “Federal Property Management” approved by the Government of the Russian Federation, in terms of securing property on the right of economic management for federal state unitary enterprises (FSUE) under the jurisdiction of the Federal Agency for State Property Management (Rosimushchestvo), in order to maintain the objects in proper condition technical condition, commercial use, reduction of facilities, not involved in economic turnover, replenishment of the federal budget. The purpose of the work is to propose ways to organize a management mechanism at the federal level aimed at using extra-budgetary mechanisms for maintaining federally owned facilities or properties and involving them in economic turnover with the involvement of commercial organisations —FGUP. The proposed ways and methods of management may allow using a more flexible mechanism for the extra-budgetary maintenance of federally owned real estate objects, their commercial use, involvement in economic turnover, with the transfer of part of the income received to the federal budget or their use for the purchase of both real estate objects for state needs based on a decision of the Government of the Russian Federation and movable property with subsequent transfer to the Treasury of the Russian Federation.